Nomenclatural changes in the genus Bambusananus Li & Xing, 2011 (Hemiptera: Cicadellidae: Deltocephalinae: Athysanini) - Xing, Ji-Chun; Chen, Xiang-Sheng (Zootaxa, 2013)
Li & Xing (in Li et al., 2011) established the leafhopper genus Bambusananus with the type species Bambusananus furcatus Li & Xing, 2011 from China. At the same time, three new combinations: Bambusananus binotatus (Li & Dai, 2003), Bambusananus bipunctatus (Li, 1999) and Bambusananus maculipennis (Li & Wang, 1993) were proposed (all species previously placed in the genus Sorhoanus). Subsequently, Yang & Chen (2012) reviewed the genus and described a new species, Bambusananus lii Yang & Chen, 2012. Presently, Bambusananus contains five species.